Ab initio three-loop calculation of the W-exchange contribution to nonleptonic decays of double charm baryons - Gutsche Th. Thomas; Ivanov M. A. Mikhail Alekseevich; Korner J. C. Jurgen; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Tyulemisov Zh. Zhomart (2019, 2019)
Title screen